2019
DOI: 10.1038/s41598-019-38987-9
|View full text |Cite
|
Sign up to set email alerts
|

Salt content dependent dielectric properties of pistachios relevant to radio-frequency pasteurization

Abstract: This study was conducted to investigate the effect of salt content during radio-frequency (RF) heating on rate of temperature increase, dielectric properties (DPs), and reduction of pathogens in pistachios. Also, the effect of RF heating on pistachio quality of varying salt content was determined. Pistachios of different salt content (0, 100, and 330 mg sodium/serving) were inoculated with Salmonella enterica and treated in a 27.12-MHz RF heater. The RF heating rate increased when salt content was in the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The nonsignificant effect of salt on ε′ is in accordance with the observations presented by other researchers for various food materials [24,34,35]. The nonsignificant effect may be because the added salts can decrease the water activity and diminish the polarization characteristics [25]. In this research, the addition of an electrolyte (NaCl) did not considerably affect ε′; however, the addition did have a marked effect on ε″.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The nonsignificant effect of salt on ε′ is in accordance with the observations presented by other researchers for various food materials [24,34,35]. The nonsignificant effect may be because the added salts can decrease the water activity and diminish the polarization characteristics [25]. In this research, the addition of an electrolyte (NaCl) did not considerably affect ε′; however, the addition did have a marked effect on ε″.…”
Section: Resultssupporting
confidence: 90%
“…The addition of salt to the material could trigger large-scale electrophoretic migration when placed in an electric field, which would promote an increase in ε″ by ionic conduction. The dielectric response of salts is closely connected with the effective nuclear charge and depends on the volume and charge of dissolved salt ions [25]. Ionic conduction mainly occurs in the RF range, and dipole rotation is the main functional mechanism of dielectric heating in the MW range [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, E. coli, S. Typhimurium and B. cereus (vegetative cell) inoculated on RGP were inactivated effectively by RF heating. Previous studies also reported that RF heating can be applied effectively to control foodborne pathogens in low water activity foods such as red and black pepper (Kim et al 2012b;Jeong and Kang 2014), raw shelled almonds (Jeong et al 2017), pistachios (Jeong et al 2019) and cumin seeds (Chen et al 2019). For example, Kim et al (2012b) reported that 50 s RF heating resulted in maximum 4Á29 log reduction of E. coli O157:H7 or S. Typhimurium in black pepper and> 5 log reduction in red pepper without colour change.…”
Section: Discussionmentioning
confidence: 98%
“…Radio frequency heating was conducted with a previously described (Jeong et al . 2019) RF heating system (Seoul National University, Seoul, South Korea; Dong Young Engineering CO. Ltd, Gyeongnam, South Korea). An RF electric field with a frequency of 27·12 MHz was generated between two parallel‐plate electrodes (30·0 × 35·0 cm; 0·6 cm thick) spaced 8 cm apart.…”
Section: Methodsmentioning
confidence: 99%